Address by Irina Bokova, Director-General of UNESCO, on the occasion of signature of the agreement between UNESCO and the Republic of Iceland, for the Vigdís International Centre for Multilingualism and Intercultural Understanding, Category 2 Centre; UNESCO, 27 June 2013 - UNESCO. Director-General, 2009-2017 (Bokova, I.G.) (27 June 2013, 2013)
Electronic version only